Reconstruction of English language teaching through contemporary Islamic thought: A conceptual study - Rinaldi Rinaldi; Sakhmalsyah Bahtiar; Muhammad Rhafi Harlan; Siti Amilah; Patmawati (Universitas Islam Negeri Ar-Raniry, 2026)
This conceptual paper examines the need to reconstruct English Language Teaching (ELT) paradigms within Islamic educational contexts through the lens of contemporary Islamic thought. In many religious educational institutions, ELT often faces a dichotomy between secular linguistic instruction and Islamic moral values. While previous studies have attempted to integrate Islamic values into ELT, most approaches remain additive and do not sufficiently address the philosophical foundations of language education. This study employs a qualitative conceptual research design based on systematic library research and content analysis to synthesize contemporary Islamic pedagogical principles with current ELT theories and practices. Through a process of conceptual synthesis, the research develops a theoretical framework that integrates Islamic ontological and epistemological perspectives into three key dimensions of ELT: curriculum design, instructional materials, and pedagogical practices. By de-westernizing materials and repositioning teachers as murabbi, the reconstruction offers a model where English proficiency and Islamic identity coexist synergistically. The analysis suggests that integrating Islamic values should move beyond superficial content inclusion toward a deeper philosophical realignment of language education. The proposed framework contributes theoretically to the discourse on culturally and religiously responsive ELT and offers conceptual guidance for educators in Islamic institutions seeking to balance global linguistic competence with the preservation of religious identity in the digital era.